Free immunoglobulin light chain (FLC) promotes murine colitis and colitis-associated colon carcinogenesis by activating the inflammasome - Junfan Ma (Nature Portfolio, 2017)
Abstract Numerous studies have demonstrated that free Ig light chain (FLC), a novel inflammation mediator, participates in many inflammatory diseases by activating mast cells and extending the survival of neutrophils. However, it remains unclear whether FLC is involved in colitis and colitis-associated colon carcinogenesis (CAC). In this study, we found a significant increase in FLC in murine models of DSS (Dextran Sulfate Sodium Salt)-induced colitis and CAC compared to controls. Peptide F991, a functional blocker of FLC, significantly attenuated colitis progression, which included abrogating the development of diarrhea and tumor burden, elevating survival rate, greatly reducing the infiltration of inflammatory cells (such as ROS+ active neutrophils), especially reducing tumorigenesis in CAC. Furthermore, we demonstrated that F991 inhibited the activation of the inflammasome by reducing the expression of cleaved caspase-1 and the maturation of IL-1β and IL-18. Altogether, our findings demonstrate that FLC can promote the pathogenesis of colitis and CAC and may be used as novel biomarker for the diagnosis of inflammatory bowel disease. Additionally, F991 may become a potential therapeutic option for colitis or colorectal cancer.